Four New Polyprenylated Acylphloroglucinols from Hypericum perforatum L. - Xiaoying Wang; Wuyang Liu; Sheng Chen; Yueshan Gao; Junmian Tian; Jinming Gao (Molecules, 2024)
Hyperforatums A–D (1–4), four new polyprenylated acylphloroglucinols, together with 13 known compounds were isolated and identified from the aerial parts of Hypericum perforatum L. (St. John’s wort). Their structures were confirmed with a comprehensive analysis comprising spectroscopic methods, including 1D and 2D NMR, HRESIMS, and electronic circular dichroism (ECD) calculations. Hyperforatum A featured an unusual chromene-1,4-dione bicyclic system, and hyperforatums B and C were two rare monocyclic PPAPs with five-membered furanone cores. Compound 1 exhibited a moderate inhibition effect on NO production in BV-2 microglial cells stimulated by LPS.